Automotive Engines: Diagnosics , Repair , Rebuilding - Gilles Tim (Thomson Delmar Learning, 2007)
Updated to reflect current trends and industry concerns, the fourth edition of Automotive Engines aids readers as they develop the technical expertise and critical thinking skills needed to effectively diagnose and troubleshoot worn and failed parts. Health and safety are emphasized throughout, with new information included on Material Safety Data Sheets, hazardous materials, personal protective equipment, and cleaning solvents. In addition to hundreds of new photographs, interesting case histories, and an entire chapter devoted exclusively to diagnosing engine problems, this edition features expanded coverage of: compression and block check tests, thinwall guide liners and insert guides, cylinder bore wear limits, rings, synthetic oils, belts, and gasket and seal technologies. High performance aspects of engine rebuilding are also introduced in an expanded chapter on CAMs, manifolds, turbochargers, and superchargers. Finally, each chapter contains carefully selected review questions to underscore key points and aid readers in gauging their understanding of essential information as they progress through the book.